1995
DOI: 10.1007/bf00214181
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a cholesterol-lowering gene in a French-Canadian kindred with familial hypercholesterolemia

Abstract: We describe a four-generation kindred with familial hypercholesterolemia (FH) in which two of the eight heterozygotes for a 5-kb deletion (exons 2 and 3) in the low density lipoprotein (LDL) receptor gene were found to have normal LDL-cholesterol levels. In our search for a gene responsible for the cholesterol-lowering effect in this family, we have studied variation in the genes encoding the LDL receptor, apolipoprotein (apo) B, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, apoAI-CIII-AIV, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…LDL-R mRNA in LDL-R ⌬5kb Fibroblasts-Although LDL-R activity in LDL-R ⌬5kb fibroblasts was only 50 -60% that of normal cells, the ratio of LDL-R mRNA to that for ␤-actin in fibroblasts and in lymphocytes was similar in carriers and non-carriers (7). To compare the relative amount of LDL-R mRNA corresponding to the deleted allele with that of the normal allele, primers surrounding the deletion were designed (see "Materials and Methods").…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…LDL-R mRNA in LDL-R ⌬5kb Fibroblasts-Although LDL-R activity in LDL-R ⌬5kb fibroblasts was only 50 -60% that of normal cells, the ratio of LDL-R mRNA to that for ␤-actin in fibroblasts and in lymphocytes was similar in carriers and non-carriers (7). To compare the relative amount of LDL-R mRNA corresponding to the deleted allele with that of the normal allele, primers surrounding the deletion were designed (see "Materials and Methods").…”
Section: Resultsmentioning
confidence: 93%
“…Oligonucleotides were synthesized by the solid phase triester method on a Pharmacia LKB Gene Assembler Plus DNA synthesizer. The ratio of fibroblast and lymphocyte LDL-R mRNA to that for ␤-actin was quantified by RT-PCR and fluorescence DNA detection as described (7). In LDL-R ⌬5kb HTZ cells, the relative expression of the deleted versus the normal LDL-R allele was determined by amplification of the cDNA with fluorescent primers 5Ј-cgccgcggcggggactgcag-3Ј and 5Ј-agttttcctcgtcagtttgtc-3Ј, yielding polymerase chain reaction fragments of 638 and 441 nucleotides for the normal and deleted allele, respectively.…”
mentioning
confidence: 99%
“…Neither the genetic nor the physiologic basis for the low apoAI are known. Many of the subjects in the kindreds reported by Fazio et al [1991], Hobbs et al [1989], and Sass et al [1995] also presented with low levels of HDL and apoAI. It is not clear, whether this is a coincidence or a characteristic of non-apoB-linked FHBL kindreds.…”
Section: Discussionmentioning
confidence: 91%
“…In 1 kindred with FHBL, linkage to apoB has been ruled out, but the gene responsible was not identified [Fazio et al, 1991]. In 2 kindreds with familial hypercholesterolemia (FH) the segregation of a ''cholesterol suppressor gene'' that produces lower than expected cholesterol levels has been noted [Sass et al, 1995;Hobbs et al, 1989]. The responsible genes are unknown, but the apoB gene has been ruled out.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, there is an extreme variability of the hypercholesterolemic phenotype with well-documented cases of incomplete penetrance probably due to the effect of modifier factors. For example, Sass et al 19 reported a French Canadian family with a 5 kb deletion in the LDLR gene with several carriers of the mutation presenting normal cholesterol values. In the same manner, Hobbs et al 20 described a large Puerto Rican family carrying the p.Ser156Leu (now p.Ser177Leu according to the international nomenclature) mutation of the LDLR gene.…”
Section: Discussionmentioning
confidence: 99%